Methionine synthase reductase A66G polymorphism and ischemic stroke in younger patients - O. V. Tsyganenko; L. I. Volkova; A. M. Alasheev (Неврология, нейропсихиатрия, психосоматика, 2021)
In the past decade, stroke incidence in younger adults increased. Methionine synthase reductase (MTRR) A66G polymorphism is one of the risk factors for ischemic stroke (IS). However, clinical features of IS in MTRR A66G polymorphism are not yet studied.Objective: to investigate clinical features of IS in MTRR A66G polymorphism.Patients and methods. One hundred forty-one younger patients with IS, hospitalized in the neurological department of Sverdlovsk Regional Clinical Hospital №1, were included in the study. MTRR A66G polymorphism was detected by the real-time polymerase chain reaction in all participants.Results and discussion. MTRR A66G polymorphism was present in 83.7% of younger patients with IS. Participants with MTRR A66G polymorphism had a significantly higher prevalence of arterial hypertension (р=0.029). In addition, protein C level was significantly lower in patients with MTRR A66G mutation (р=0.001).Conclusion. The majority of younger patients with IS have MTRR A66G polymorphism. Therefore, the inclusion of MTRR A66G polymorphism screening in the diagnostic algorithm of stroke in young adults seems necessary.